دور الاثصال امترويجي في تحسين امصورة الذىنية نومؤسسة - بوعموفة حشاف; -مسعود زريق; د/حجاج مجاني (جامعة عمار ثليجي الاغواط, 2023)
مخلص الدراسة: هدفت دراستنا الى التعرف على دور الاتصال الترويجي في تحسين الصورة الذهنية للمؤسسة وجاءت هذه الدراسة بمؤسسة جيزي، وانطلقت من إشكالية ما دور الاتصال الترويجي في تحسين الصورة الذهنية للمؤسسة؟ وأجريت الدراسة على عمال مؤسسة جيزي بالأغواط والبالغ عددهم 20 عاملا وعاملة، وتم الاستعانة بالمنهج الوصفي واداة جمع البيانات الاستبيان وتم الوصول الى النتائج التالية: 1. للاتصال الترويجي دورا في ابراز خدمات المؤسسة لجمهورها من خلال الرسائل التي يقدمها والمتمثلة في الاشهارات والاعلانات والخدمات الراقية والتنافسية وهذا ما يجعل الجمهور يلتف حول المؤسسة ويشترك بخدمته. 2. الاساليب الاتصالية المستخدمة بمؤسسة جيزي بالأغواط تحسن من صورة المؤسسة لدى جمهورها الخارجي من خلال التسهيلات المقدمة والاتصال الدائم بين المؤسسة والجمهورية 3. مؤسسة جيزي تعتمد على الاتصال الترويجي لتوطيد العلاقة بينها وبين جمهورها ورسم صورة ذهنية جيده لدى جمهورها اداه الوصل بينهما. 4. آراء الجماهير تؤخذ بعين الاعتبار بمؤسسة جيزي من الاغواط وهذا ما يفسر اعتمادها على صبر الآراء دوما من اجل اخذ اراء جمهورها وتصحيح ما يصحح ومعالجة ما يعالج والتطوير من الخدمات الجيد. الكلمات المفتاحية: الدور - الاتصال الترويجي – تحسين – الصورة الذهنية – المؤسسة study savior: Our study aimed to identify the role of promotional communication in improving the mental image of the institution The study was conducted on the 20 workers of the Djezzy Foundation in Laghouat, and the descriptive approach and the questionnaire data collection tool were used, and the following results were reached: 1. Promotional communication plays a role in highlighting the institution's services to its audience through the messages it provides, which are represented in advertisements, high-end and competitive services, and this is what makes the audience rally around the institution and participate in its service. 2. The communication methods used by the Djezzy Foundation in Laghouat improve the image of the institution to its external audience through the facilities provided and the permanent contact between the institution and the republic 3. Jeezy Foundation relies on promotional communication to consolidate the relationship between it and its audience and to draw a good mental image among its audience as a linking tool between them. The opinions of the masses are taken into account in the Djezzy Foundation, and this explains its reliance on the patience of opinions always in order to take the opinions of its audience, correct what is corrected, deal with what is treated, and develop good services. key words: Role - Promotional Communication - Improving - Mental Image - Institution
)دراسة حالة مؤسسة جيزي با أ لغواط (